PERUBAHAN FASADE RUMAH DI PERUMAHAN WONINGPARK GERGAJI SEMARANG - Burhan Arif (Diponegoro University, 2014)
[Title: A Change of The Facade of a House in Recidential Woningpark Gergadji Semarang] Indis architecture is an assimilation or a mixture of elements of Western culture especially the Dutch with Indonesian culture, especially from Java. Woningpark Gergadji (Park Housing Gergadji or NIS - Park) is a residential complex that is occupied by employees and their families who work in the NIS / Nederlands Indische Spoorweg Maatschapij (now PT . KAI DAOP IV) since the Dutch colonial era. The houses in the housing preserved and maintained . But now every home no longer has the same view of the facade as the first appearance of the facade of the colonial period look even additional buildings that resemble a home between homes - the original home. This thesis discusses a changes the facade of the main house at Recidential Woningpark Gergadji performed by residents since occupied. If there is a change of the facade that does not follow the rules that match the architecture of the building, it will make the facades of the building will lose its identity. A growing phenomenon in that houses, there is a change in the facade of the main building and the new building increased in the land. Therefore, the PT. KAI DAOP IV and residents today must work well together so that the houses retaining the architectural identity.